A specific transitory increase in intracellular calcium induced by progesterone promotes acrosomal exocytosis in mouse sperm - Romarowski, Ana (2016)
During capacitation, sperm acquire the ability to undergo the acrosome reaction (AR), an essential step in fertilization. Progesterone produced by cumulus cells has been associated with various physiological processes in sperm, including stimulation of AR. An increase in intracellular Ca2+ ([Ca2+]i) is necessary for AR to occur. In this study, we investigated the spatio- temporal correlation between the changes in [Ca2+]i and AR in single mouse spermatozoa in response to Progesterone. We found that Progesterone stimulates an [Ca2+]i increase in five different patterns: gradual increase, oscillatory, late transitory, immediate transitory and sustained. We also observed that the [Ca2+]i increase promoted by Progesterone starts at either the flagellum or the head. We validated the use of FM4-64 as an indicator for the occurrence of the AR by simultaneously detecting its fluorescence increase and the loss of EGFP in transgenic EGFPAcr sperm. For the first time, we have simultaneously visualized the rise in [Ca2+]i and the process of exocytosis in response to Progesterone and found that only a specific transitory increase in [Ca2+]i originated in the sperm head promotes the initiation of AR.